Synthesis, Structure and Cytotoxicity of N, N and N, O‐Coordinated RuII Complexes of 3‐Aminobenzoate Schiff Bases against Triple‐negative Breast Cancer. Issue 22 (11th October 2021) - Mukherjee, Arpan; Koley, Tuhin Subhra; Chakraborty, Ayan; Purkait, Kallol; Mukherjee, Arindam
Abstract: Half‐sandwich Ru II complexes, [(YZ)Ru II (η 6 ‐arene)(X)]+, (YZ=chelating bidentate ligand, X=halide), with N, N and N, O coordination (1 –9 ) show significant antiproliferative activity against the metastatic triple‐negative breast carcinoma (MDA‐MB‐231). 3‐aminobenzoic acid or its methyl ester is used in all the ligands while varying the aldehyde for N, N and N, O coordination. In the N, N coordinated complex the coordinated halide(X) is varied for enhancing stability in solution (X=Cl, I). Rapid aquation and halide exchange of the pyridine analogues, 2 and 3, in solution are a major bane towards their antiproliferative activity. Presence of free −COOH group (1 and 4) make complexes hydrophilic and reduces toxicity. The imidazolyl 3‐aminobenzoate based N, N coordinated 5 and 6 display better solution stability and efficient antiproliferative activity (IC50 ca. 2.3–2.5 μM) compared to the pyridine based 2 and 3 (IC50 >100 μM) or the N, O coordinated complexes (7 –9 ) (IC50 ca. 7–10 μM). The iodido coordinated, 6, is resistant towards aquation and halide exchange. The N, O coordinated 7 –9 underwent instantaneous aquation at pH 7.4 generating monoaquated complexes stable for at least 6 h. Complexes 5 and 6, bind to 9‐ethylguanine (9‐EtG) showing propensity to interact with DNA bases. The complexes may kill via apoptosis as displayed from the study of 8 . The change in coordination mode and the aldehyde affected the solution stability, antiproliferative activity and mechanistic pathways. The N, N coordinated (5 and 6 ) exhibit arrest in the G2/M phase while the N, O coordinated 8 showed arrest in the G0/G1 phase. Abstract : 3‐Aminobenzoate based N, N and N, O coordinated Ru II complexes of various aldehydes show imidazole based N, N coordinated complexes are more stable and better cytotoxic against the TNBC, MDA‐MB‐231 (eight times more toxic than oxaliplatin), in comparison to the N, O coordinated ones. DNA is one of the targets to kill via apoptosis although the alteration of the aldehyde varies the cell cycle arrest from G0/G1 to G2/M.